(untitled) (Research, Society and Development, 2022)
Gastric cancer is a major public health problem, considered the fifth most frequently diagnosed cancer worldwide. Peritoneal metastasis is the main causes of mortality related to gastric cancer. The hypermethylation of tumor suppressors genes is a promising factor for the development of predictive biomarkers. In gastric tumors, reduced expression of CDH1 suppressor gene contributes to tumor invasion and triggering metastasis. We aim to evaluate the promoter region methylation profile of the CDH1 gene as a peritoneal metastasis indicator in patients with gastric cancer. CDH1 methylation profile were evaluate in 47 samples of peritoneal washes from patients with gastric cancer by bisulfite sequencing PCR (BSP). Thirty-three CpGs sites in the CDH1 promoter region were individually evaluated. Samples with ≥ 10% of methylated CpGs sites were considered hypermethylated. Statistical analysis was performed by Fisher’s Exact test using R-Studio program (p≤0.05). Twenty-nine (62%) samples showed hypermethylation in the promoter region of CDH1, with preferential methylation at the CpGs sites located in the region 5’ upstream from gene. Statistical analysis showed that CDH1 hypermethylation was significantly different in patients with advanced stages of tumor depth of invasion (p=0.03). Our results suggest that CDH1 gene methylation analysis is a useful tool in predicting tumor progression and invasiveness in gastric cancer patients and could have a major impact for the field of precision cancer medicine.